2013
DOI: 10.3390/ijms140612401
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Recombinant Ricin Toxin Binding Subunit B (RTB)

Abstract: Ricin toxin binding subunit B (RTB) is one of the subunits of the ricin protein. RTB has been used as adjuvant, but little is known about its mechanism. In this study, we found that RTB increased not only nitric oxide (NO) release, but also tumor necrosis factor (TNF)-α and interleukin (IL)-6 production in mouse macrophage cell line RAW264.7 cells. They subsequently exhibited enhanced ConA-induced T-cell and LPS-induced B-cell proliferative responses. We also examined the cytokines that were produced from sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…14,15,17 And compared with the prophylactic or therapeutic vaccine against RT or AT published previously, 1-10 the chimeric protein vaccine exhibits several advantages as described above. Therefore, we developed a chimeric protein vaccine and investigated the immunogenicity and protective immunity generated by vaccination of RTB-ATB without adjuvant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…14,15,17 And compared with the prophylactic or therapeutic vaccine against RT or AT published previously, 1-10 the chimeric protein vaccine exhibits several advantages as described above. Therefore, we developed a chimeric protein vaccine and investigated the immunogenicity and protective immunity generated by vaccination of RTB-ATB without adjuvant.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][10][11][12] However, evidences suggest that B chain may be useful as a toxin subunit vaccine. 14,15 First, B chain, in the absence of A chain, is non-toxic. Second, anti-RTB antibodies administered intravenously (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, previous studies also have demonstrated that B chain of toxins can exhibit both antigenic and adjuvant activity. 20,22,25,26 Therefore, it is seemly feasible to use ATB as a target for vaccine candidate. However, few reports have examined the use of B subunit as a vaccine candidate in humans in spite of some long-standing evidence indicating that the anti-B-subunit specific antibodies have the capacity of neutralizing corresponding toxin.…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports have examined the use of B subunit as a vaccine candidate in humans in spite of some long-standing evidence indicating that the anti-B-subunit specific antibodies have the capacity of neutralizing corresponding toxin. 6,20,26 In this study, we developed a B subunitbased vaccine of AT and assessed the immune response and the protective efficacy elicited by the recombinant protein without adjuvant in mice model. Firstly, the fulllength gene encoding ATB was optimized and designed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These two subunits are coupled via a single interchain disulfide bond (Lord, Roberts, & Robertus, 1994). RTB is a lectin that interacts with glycoproteins or glycolipids and with galactose‐/ N ‐acetylgalactosamine (Liu et al, 2013) to facilitate RT uptake at the cell surface. RT holotoxin undergoes retrograde translocation to the endoplasmic reticulum (ER) from the trans ‐Golgi network via endocytosis, where RTA and RTB chains are separated via a break in the single interchain disulfide bond (May, Yan, & Tumer, 2013; Spooner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%